2007
DOI: 10.1038/nn1870
|View full text |Cite
|
Sign up to set email alerts
|

TRPC channels promote cerebellar granule neuron survival

Abstract: Channels formed by the transient receptor potential (TRP) family of proteins have a variety of physiological functions. Here we report that two members of the TRP cation channel (TRPC) subfamily, TRPC3 and 6, protected cerebellar granule neurons (CGNs) against serum deprivation-induced cell death in cultures and promoted CGN survival in rat brain. In CGN cultures, blocking TRPC channels or downregulating TRPC3 or 6 suppressed brain-derived neurotrophic factor (BDNF)-mediated protection, BDNF-triggered intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
220
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(238 citation statements)
references
References 49 publications
17
220
0
1
Order By: Relevance
“…It is also worth noting that oxidative stress has been shown to activate TRPC3 and TRPC4 in endothelial cells (23) and that another submember of TRP channels, TRPM, has been reported to contribute to oxidative stress-induced cell death (23). However, in contrast to these reports suggesting that TRPCs contribute to increased cell death, Jia et al (16) showed that TPRC3 and TRPC6 played a role in promoting neuronal survival in response to serum deprivation. Taken together with our results, these studies support the notion that TRPCs play a role in regulating cell survival; however, whether they contribute to cell death or survival may be both cell and stress specific.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that oxidative stress has been shown to activate TRPC3 and TRPC4 in endothelial cells (23) and that another submember of TRP channels, TRPM, has been reported to contribute to oxidative stress-induced cell death (23). However, in contrast to these reports suggesting that TRPCs contribute to increased cell death, Jia et al (16) showed that TPRC3 and TRPC6 played a role in promoting neuronal survival in response to serum deprivation. Taken together with our results, these studies support the notion that TRPCs play a role in regulating cell survival; however, whether they contribute to cell death or survival may be both cell and stress specific.…”
Section: Discussionmentioning
confidence: 99%
“…Such phytochemicals can induce a mild adaptive stress response in cells. Examples include resveratrol, a chemical in red wine that may protect against cardiovascular disease, which induces a stress resistance response mediated by a protein called Sir-2 (Tissenbaum and Guarente, 2001;Howitz et al, 2003); sulforaphane and curcumin, which are present at high levels in broccoli and curry powder, respectively, and activate the Nrf-2-antioxidant response element pathway resulting in the expression of phase 2 detoxifying and antioxidant enzymes (Faulkner et al, 1998); and allicin, from garlic, which activates transient receptor potential receptors, resulting in calcium influx and downstream signaling cascades that upregulate neurotrophic factor expression (Macpherson et al, 2005;Jia et al, 2007). Therefore, from both evolutionary and mechanistic perspectives, at least some beneficial effects of phytochemicals in the human diet may be mediated by hormetic mechanisms.…”
Section: Diet and Neurohormesismentioning
confidence: 99%
“…To determine whether PLC␥, PI(3)K, and protein tyrosine kinase were involved in activation of TRPC5 channels leading to neurite outgrowth, pharmacological blockers for tyrosine kinase (genistein), PLC (U73122), and PI(3)K (wortmannin, LY294002) were used. These widely used inhibitors were reported to show specificity for the indicated reactions (Akiyama et al, 1987;Bleasdale et al, 1990;Powis et al, 1994;Vlahos et al, 1994;Laurino et al, 2005;Li et al, 2005;Jia et al, 2007). In some cases, ATP, known to activate TRPC5 channels via PLC through stimulation of G-protein-controlled signaling (Shimizu et al, 2006), was also applied subsequent to CtxB.…”
Section: Activation Of Integrin Signaling Cascade By Ctxbmentioning
confidence: 99%